Chronic spontaneous and inducible urticaria 2 - Maurer, Marcus (Henry Stewart Talks, 2020)
CIndU (Chronic Inducible Urticaria) diagnostic workup, Symptomatic dermographism, Tests to identify CIndU, Therapeutic strategies of chronic urticaria (CU), CU treatment algorithm, Treatment with omalizumab, Ligelizumab vs. Omalizumab, Future treatments